How far is too far? A nationwide cross-sectional study for establishing optimal hospital access time for Korean pregnant women - Mi Young Kwak; Seung Mi Lee; Hyun Joo Kim; Sang Jun Eun; Won Mo Jang; Hyemin Jung; Yoon Kim; Jin Yong Lee (BMJ Open)
Objectives Access to a delivery unit is a major factor in determining maternal morbidity and mortality. However, there is little information about the optimal access time to a delivery unit. This study aimed to establish the optimal hospital access time (OHAT) for pregnant women in South Korea.Design Nationwide cross-sectional study.Setting We used the National Health Insurance System database of South Korea.Participants We analysed the data of 371 341 women who had experienced pregnancy in 2013.Primary and secondary outcome measures Access time to hospital was defined as the time required to travel from the patient’s home to the delivery unit. The incidence of obstetric complications was plotted against the access time to hospital. Change-point analysis was performed to identify the OHAT by determining a point wherein the incidence of obstetric complications changed significantly. As a final step, the risk of obstetric complications was compared by type among pregnant women who lived within the OHAT against those who lived outside the OHAT.Results The OHAT associated with each adverse pregnancy outcomes were as follows: inadequate prenatal care, 41–50 min; preeclampsia, 51–60 min; placental abruption, 51–60 min; preterm delivery, 31–40 min; postpartum transfusion, 31–40 min; uterine artery embolisation, 31–40 min; admission to intensive care unit, 31–40 min; and caesarean hysterectomy, 31–40 min. Pregnant women who lived outside the OHAT had significantly higher risk for obstetric complications than those who lived within the OHAT.Conclusions Our results showed that the OHAT for each obstetric complication ranged between 31 and 60 min. The Korean government should take the OHAT under consideration when establishing interventions for pregnant women who live outside OHAT to reduce maternal morbidity and mortality.